Supramolecular fabrication of multilevel graphene-based gas sensors with high NO2 sensibility1. Issue 22 (14th June 2015) - Chen, Zhuo; Umar, Ahmad; Wang, Shiwei; Wang, Yao; Tian, Tong; Shang, Ying; Fan, Yuzun; Qi, Qi; Xu, Dongmei; Jiang, Lei
<x xml:space="preserve">Abstract</x> This work reports the supramolecular assembly of a silver nanoparticle-naphthalene-1-sulphonic acid-reduced graphene oxide (Ag-NA-rGO) composite and its utilization to fabricate a highly sensitive and selective gas sensor.